Síntese one-pot de biodiesel aditivado utilizando reator de micro-ondas (2450 MHz) - Marques, Matheus Zimermann (2020)
Biodiesel is the direct substitute for diesel oil and can be used directly in diesel engines or in varying proportions of diesel and biodiesel. It is a sustainable fuel due to the fact that it is synthesized from vegetable oils and a short-chain alcohol in the presence of an acid or basic catalyst. For every 3 moles of biodiesel produced, 1 mole of glycerol is generated as a co product, and this represents approximately 10% by weight in relation to the reagents. However, the market does not have a high demand for glycerol as it does for biodiesel, and for this purpose new methodologies have been developed to transform glycerol into a product with high added value so that it can be sold for a higher price or turn it into an additive. that improves the properties of biodiesel during its combustion in diesel engines. The objective of this work was to synthesize a biodiesel where the glycerol generated was later converted into an oxygenated additive for the biodiesel itself using a microwave reactor operating at the frequency of 2450 MHz and a single-mode applicator as a heating source. The acid catalysts tested in this work were H2SO4, pTol-SO3H, CH3SO3H, DB-SO3H and FeCl3 ∙ 6H2O. Of these catalysts, only DB-SO3H was able to perform the transesterification of refined soybean oil with anhydrous ethanol with high conversions for the power used in the microwave reactor (1200 W). Despite producing high conversions in the acid transesterification of oil and ethanol, the catalyst carried out parallel reactions in the unsaturation of AGs. The study of acetalisation of glycerin P.A. using 600 W power from the reactor used 3 synthesis methodologies to shift the reaction equilibrium. The most promising is based on removing the hydrated acetone by distillation, with constant additions of anhydrous acetone being carried out to keep the level of acetone in the reactor stable. The best experimental condition obtained was using a molar ratio of 1: 6 glycerol: acetone with 0.22% FeCl3 ∙ 6H2O (w/w), reaching a conversion of 81.25% in 1 min and 99.90% in 15 minutes reaction. Microwave-induced heating accelerated the reaction rate compared to other studies of homogeneous acid catalysts in the literature. Acetalisation of the glycerol obtained after transesterification of soybean oil with ethanol using 2.43% w/w DB-SO3H indicated the presence of solketal by 1H NMR with only 1 min of microwave irradiation at 600 W power of the reactor. It was not possible to quantify the solketal produced in this reaction by CG-DIC because it was not possible to efficiently remove the catalyst from the reaction by any tested purification method. The microwave-induced acetalisation products of glycerol with acetone were purified and characterized. Microwave-induced heating accelerated the reaction rate compared to other studies of homogeneous acid catalysts in the literature. One-pot acetalisation proved to be possible for the DB-SO3H catalyst, but its removal at the end of the process is difficult to perform. This work provides a viable method using homogeneous catalysis for large-scale implementation of solketal synthesis using low cost and non-toxic acid catalysts for the operator.